THE IMPACT OF ECONOMIC SANCTIONS ON GLOBAL POLITICS: EFFECTIVENESS AND ETHICAL ISSUES - Wali Muhammad; Dr Nadia Zaheer Ali; Mohammad Jahangir Khan; Sobia Saeed; Kamaran Qader Yaqub; Anjuman Awal (Policy Research Journal, 2025)
Sanctions have become an important tool of state policy in the sphere of international relations, responding to various challenges, including nuclear danger, violations of human rights, and disputed territories. This article aims to analyze the published data around the globe and its efficacy and morality of the economic sanctions to achieve these goals at the targeted country and population. Based on the case analysis of sanctions like those on Iran, North Korea, and Russia, the study assesses their political and economic consequences, especially on the unintended emergence of humanitarian crises and various struggles of civilian populations. The data was analyzed in three steps. The following issues are highlighted here—the potential adverse effects on minority populations and questions of whether such sanctions are ethically defensibly at all. Based on the analysis, the article suggests some measures to strengthen the efficiency of sanctions and address the visionary ethical issues in world politics.